The efficiency of monotherapy of patients with primary open-angle glaucoma with Bimatoprost 0.03 % (Bimoptic) - S. A. Korotkikh; G. V. Zhiborkin; E. S. Knyazeva; L. V. Rusakova (Российский офтальмологический журнал, 2018)
Purpose: to evaluate the hypotensive effect and adverse reactions occurrence in patients with primary open angle glaucoma (POAG) who received Bimatoprost (Bimoptic Rompharm) monotherapy.Materials and methods. 46 patients (75 eyes) with stage I–III POAG were prescribed bimatoprost therapy. Of these, 16 patients (20 eyes) had newly diagnosed glaucoma, 15 patients (27 eyes) previously received treatment with prostaglandin analogs (APG — Latanoprost), and 15 patients (28 eyes) previously received treatment with a fixed combination (FC) composed of timolol B-blocker and brinzolamide carbonic anhydrase inhibitor. The reason for transferring the patient from therapy with APG and FC to monotherapy with Bimatoprost was insufficient hypotensive effect of APG/FC therapy, and the presence of dry eye syndrome of varying severity in most patients. The results were evaluated after 1, 4 and 12 weeks of Bimatoprost therapy. Results. A hypotensive effect of monotherapy with Bimatoprost was confirmed in patients with newly diagnosed POAG. An additional hypotensive effect was revealed when patients with POAG were transferred from APG and FC therapy to monotherapy with Bimatoprost. Adverse reactions: mild and moderate hyperaemia, periorbital manifestations such as skin pigmentation, deepening of upper eyelid folds, narrowing of the palpebral fissure (ptosis) were noted, respectively, in 8, 6.7, 1.3, 2.7, 2.7 % of cases respectively, but did not require a discontinuation of the therapy in any patient. Eyelash growth was noted by 3 patients (4 %). This effect was not considered to be a side effect, since none of the patients bothered. In 47 % of patients who had previously received APG and FC therapy and had dry eye syndrome of varying severity, objective and subjective positive changes relating to dry eye syndrome was noted. A positive dynamic of morphometric parameters of the optic nerve and cells of the retinal ganglion complex was revealed in patients of all groups of study.Conclusion. Monotherapy with Bimatoprost can be recommended as therapy of choice for patients with newly diagnosed glaucoma, and those previously receiving antihypertensive therapy with PGAs or fixed combinations (-blocker + carbonic anhydrase inhibitor) including those having dry eye  syndrome of varying severity.